Performance Enhancement With Triangular Loop Frequency Selective Surface On Microstrip Array Antenna For 5G Application - Abd Rahim, Muhamad Akliff (2018)
The Fifth generation communication offers many benefits such as massive system capacity,very high data rate and low latency.Microstrip array antenna were popular due to the easiness of design and fabrication process.Besides, the microstrip array antenna is also popular for backhaul application. To enhance the performance of microstrip array antenna,the FSS has been integrated to the antenna structure.The Frequency Selective Surface (FSS) is based on metamaterial are the substitute to the fixed frequency metamaterials with static geometry and spacing in the unit cells used to find out the frequency response of a given metamaterial.FSS with specific geometrical shapes can be made-up as periodic arrays with elements of two dimensional.Antenna specification for return loss is below than -10 dB,but in practical field,the reflection coefficient of the signal always fluctuates,so it is giving unstable value for return loss.The directivity of the antenna depends on the antenna design.Since this antenna element is microstrip array antenna,the antenna performance will change by the additional patch.The integration with the FSS will be affected towards the return loss of the antenna.The design of antenna and Frequency Selective Surface is at 28 GHz on the Rogers Duroid RT5880 board with the thickness of substrate is 0.254 mm and copper thickness is 0.017 mm with dielectric constant of 2.2 and the tangent loss is 0.0009.The antennas was design from single patch antenna until 32-element patch array antenna by using the quarter wave theory to feed at 50 Ω,70 Ω and 100 Ω.The FSS design on this research was held on three designs which are triangular loop,hexagonal loop and rectangular loop.From the simulation the triangular loop had the best result on return loss is -30.832 dB at 28 GHz.The rectangular antenna has been choosen due to the best result on single design which is -49.48 dB,next the single design has evolved to 32-element patch array antenna and the result is decreased to -37.62 dB.The 32 -element patch array antenna are integrated with triangular loop FSS,the return loss is better which is -64.67 dB.The simulation is done using microwave CST software.The fabrication process involves the photo etching technique.The return loss measurement on integrated antenna with FSS gives a minimum resonant -43.55 dB at 28.45 GHz,slightly shifted from the simulation result.The antenna directivity was recorded of 21.7 dBi.